Assessment of 25-OH vitamin D levels and abnormal blood pressure response in female patients with cardiac syndrome X - Babür Güler, Gamze; Güler, Ekrem; Hatipoğlu, Suzan; Güneş, Hacı Murat; Geçmen, Çetin; Demir, Gültekin Günhan; Barutçu, İrfan (Turkish Society of Cardiology, 2016)
Objective: Vitamin D deficiency is associated with coronary artery disease, hypertension, heart failure, endothelial dysfunction, and metabolic syndrome. The pathophysiology of cardiac syndrome X (CSX) involves many pathways that are influenced by vitamin D levels. This study aimed to investigate the relationship between vitamin D deficiency and abnormal blood pressure response to exercise in patients with CSX. Methods: This was a cross-sectional and observational study. Fifty females with normal epicardial coronary arteries who presented with typical symptoms of rest or effort angina and 41 healthy age-matched female controls, were included. Patients with cardiomyopathy, severe valvular disease, congenital heart disease, and left ventricular hypertrophy were excluded. All patients underwent stress electrocardiography examination and 25-hydroxy (OH) vitamin D level measurements. Results: Levels of 25-OH vitamin D were significantly lower in CSX patients (9.8±7.3 ng/mL vs. 18.1±7.9 ng/mL; p<0.001). Systolic blood pressure (SBP) (188±15 mm Hg vs. 179±17 mm Hg; p=0.013) and diastolic blood pressure (DBP) (98±9 mm Hg vs. 88±9 mm Hg; p<0.001) during peak exercise were higher in CSX patients. Levels of 25-OH vitamin D were negatively correlated with peak SBP (r=–0.310, p=0.004) and peak DBP (r=–0.535, p<0.001) during exercise. To discard the multicollinearity problem, two different models were used for multivariate analyses. In the first model, metabolic equivalents (METs) (p=0.003) and 25-OH vitamin D levels (p=0.001) were independent predictors. METs (p=0.007), 25-OH vitamin D levels (p=0.008), and peak DBP were determined as independent predictors in the second multivariate model. Conclusion: In patients with CSX, 25-OH vitamin D levels were lower than those in controls; moreover, 25-OH vitamin D deficiency was also associated with higher levels of peak DBP during exercise.
Keywords: 25-OH Vitamin D; Abnormal Blood Pressure Response; Cardiac Syndrome X